If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9q + 3r = 15m Solving 9q + 3r = 15m Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-3r' to each side of the equation. 9q + 3r + -3r = 15m + -3r Combine like terms: 3r + -3r = 0 9q + 0 = 15m + -3r 9q = 15m + -3r Divide each side by '9'. q = 1.666666667m + -0.3333333333r Simplifying q = 1.666666667m + -0.3333333333r
| 4x+5=3x+8-x | | 11d+4=4d+39 | | 15x+10y=400 | | 12n-29=2n | | y+2x=14 | | 4a^2-3a-24=0 | | sin^2x=3cos^2x | | 75(2)= | | 2w+4x-11y+7w+10x+5y= | | 10x(0)=x | | 2/5+y-8=11 | | 2(x-9)=-15.4 | | -4v^2+32v=64 | | 9y-4y+20=40 | | 752/2= | | (6d+5)-(-2-3d)= | | 4*(10*-10)= | | 6(3m-5)=66 | | 7x-10+5x+7=-20-7 | | 21+18m=183 | | 4a^2-3a-16=0 | | x/2+8= | | 7(x-4)=-42 | | -[z-3y-(3x-z-2y)+3z+2y]-x= | | 9(a+1)=79.2 | | (16-2x)=10x | | 74=8c-2 | | -10=-5(7-5a) | | 21(24)= | | 12*0.5h=18*2h | | (9x+10)+(6x-4)= | | 9+7y=51 |